2014
DOI: 10.1620/tjem.232.263
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Plasma Galectin-9 in Patients with Influenza Virus Infection

Abstract: Galectin-9 (Gal-9) is a β-galactoside-binding protein involved in various biologic processes, including cell aggregation, adhesion, chemoattraction, and apoptosis. Little is known, however, about the regulation mechanisms of Gal-9 production. Recent studies reported high plasma Gal-9 levels in humans infected with human immunodeficiency virus-1 and dengue virus. Viral respiratory infections such as influenza are common human illnesses. A synthetic double-stranded RNA, polyinosinic-polycytidylic acid (PolyIC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…In cervical cancer, a correlation with high differentiation grade has been described for galectin-9 expression [31], in agreement with the trend toward improved prognosis described in our study. Tumor galectin-9 expression might be related to HPV infection, as different viruses including human cytomegalovirus, HIV and influenza virus have been shown to induce galectin-9 expression [4345]. We found that galectin-3 and galectin-9 expression were both significantly correlated with HPV16 or HPV18 expression, supporting this hypothesis.…”
Section: Discussionsupporting
confidence: 79%
“…In cervical cancer, a correlation with high differentiation grade has been described for galectin-9 expression [31], in agreement with the trend toward improved prognosis described in our study. Tumor galectin-9 expression might be related to HPV infection, as different viruses including human cytomegalovirus, HIV and influenza virus have been shown to induce galectin-9 expression [4345]. We found that galectin-3 and galectin-9 expression were both significantly correlated with HPV16 or HPV18 expression, supporting this hypothesis.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, individuals infected with hepatitis C virus (HCV), HIV-1, dengue virus, and influenza virus have higher serum levels of Gal-9 (6,(22)(23)(24), yet the mechanism responsible for such increases has not been identified. Given the critical role of type I IFNs in controlling viral infections, it is tempting to speculate that IFN-␤ may be an essential driver of Gal-9 upregulation.…”
Section: Upregulation Of Galectin 9 By Hcmv Is Via Induction Of Intermentioning
confidence: 99%
“…There were no current smokers at the time of the study. Smoking status had no influence on the Gal-9 levels in the BALF in a previous study [17]. Surfactant protein D and lactate dehydrogenase were similar, but Krebs von den Lungen-6 was significantly lower in patients with COP than in patients with IPF (p \ 0.05).…”
Section: Study Subjectsmentioning
confidence: 58%
“…Mouse monoclonal antibody against human Gal-9 (9S2-3) and polyclonal rabbit anti-human Gal-9 antibody were purchased from GalPharma (Takamatsu, Japan) [17]. Human lung fibroblast cells, fibroblast basal medium, and supplements for fibroblast culture were purchased from Lonza (Walkersville, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation